2007
DOI: 10.1007/s00424-007-0379-z
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine-induced Ca2+ oscillations are modulated by a Ca2+ regulation of InsP3R2 in rat portal vein myocytes

Abstract: Oscillations of cytosolic Ca2+ levels are believed to have important roles in various metabolic and signalling processes in many cell types. Previously, we have demonstrated that acetylcholine (ACh) evokes Ca2+ oscillations in vascular myocytes expressing InsP3R1 and InsP3R2, whereas transient responses are activated in vascular myocytes expressing InsP3R1 alone. The molecular mechanisms underlying oscillations remain to be described in these native smooth muscle cells. Two major hypotheses are proposed to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The InsP3R2 has the highest sensitivity to InsP3 and was regulated by Ca 2+ in a bell-shaped concentration-dependent manner, whereas the InsP3R3 has the lowest InsP3 sensitivity and was very weakly modulated by Ca 2+ in comparison with both other subtypes [36,42,53]. As we have previously shown in smooth muscle [21,39], the increase of InsP3R3 proportion could explain the decrease of the InsP3 affinity to induce Ca 2+ signals without change in the maximal Ca 2+ response. On the other hand, in MCA, the increase of InsP3R2 proportion induces a higher InsP3 affinity and leads to inhibition by Ca 2+ of InsP3 receptors [58], inducing a large modification of the maximal response as described in engineered cells expressing different combinations of InsP3R subtypes [53].…”
Section: +mentioning
confidence: 57%
“…The InsP3R2 has the highest sensitivity to InsP3 and was regulated by Ca 2+ in a bell-shaped concentration-dependent manner, whereas the InsP3R3 has the lowest InsP3 sensitivity and was very weakly modulated by Ca 2+ in comparison with both other subtypes [36,42,53]. As we have previously shown in smooth muscle [21,39], the increase of InsP3R3 proportion could explain the decrease of the InsP3 affinity to induce Ca 2+ signals without change in the maximal Ca 2+ response. On the other hand, in MCA, the increase of InsP3R2 proportion induces a higher InsP3 affinity and leads to inhibition by Ca 2+ of InsP3 receptors [58], inducing a large modification of the maximal response as described in engineered cells expressing different combinations of InsP3R subtypes [53].…”
Section: +mentioning
confidence: 57%
“…Analysis of IP 3 -induced Ca 2+ release in DT40 TKO cells expressing a single IP 3 R isoform demonstrated that DT40 TKO cells heterologously expressing a single IP 3 R isoform could sustain Ca 2+ oscillations for an extended period after stimulation by an anti B-cell receptor antibody only if the expressed isoform was IP 3 R2 [48]. Very similar results were obtained in vascular myocytes, whereby only the cells expressing IP 3 R2 in addition to IP 3 R1 displayed a Ca 2+ oscillation pattern [49, 50]. Comparison of native IP 3 R1 (from cerebellum) and IP 3 R2 (from heart) [51] or the comparative analysis of each of the three IP 3 R isoforms heterologously expressed in Sf9 insect cells [52] also confirmed the rank-order of the sensitivity of channel opening towards IP 3 as IP 3 R2 > IP 3 R1 > IP 3 R3, when measured after incorporation in planar lipid bilayers.…”
Section: Specific Molecular and Cellular Properties Of Ip3r2mentioning
confidence: 90%
“…In rat mesenteric arteries, PE-induced Ca 2+ waves were abolished by blockade of IP 3 R with 2-APB, a small-molecular-weight membrane-permeable modulator of the IP 3 R [29,48]. Furthermore, acetylcholine-induced Ca 2+ waves in rat portal vein myocytes are also dependent on activation of IP 3 Rs, mostly through the IP 3 R 2 subtype [49,50]. However, its use to block IP 3 Rs has been criticized for its nonspecific effects on other ion transport mechanisms, notably its inhibition of store-operated channels [51,52,53].…”
Section: Discussionmentioning
confidence: 99%